The diarium of Magister Johannes Kelpius - Kelpius, Johannes 1673-1708; Sachse, Julius Friedrich 1842-1919 (University Park, Pa. Metalmark Books, 2012)
"An English translation, originally published by the Pennsylvania German Society in 1917, of the diary of radical German Pietist Johannes Kelpius (1667-1708). Includes facsimile pages of his prayer book A Short, Easy, and Comprehensive Method of Prayer"--Provided by publisher
Orig. publ.: Lancaster, Pa. : Press of the New Era Print. Co., 1917
Archivierung prüfen
Keywords: Kelpius, John -- 1667?-1708 -- Diaries; Pietists -- Diaries; Briefsammlung; Tagebuch